ISRA announcement influence on Abnormal Return and Stock Trade Volume - Anggraini, Dewi (Archives of Business Research, 2018)
This study aims to analyze the influence of the Indonesia Sustainability Reporting Awards (ISRA) announcement from 2009 to 2016 on stock price, which is seen from the change of abnormal return and stock trading volume prior and after the date of the announcement. The samples for this research are publicly-listed companies that participated in ISRA from 2009 until 2016, both award winners and nonwinners. The data used are secondary data consisting of abnormal return and stock trading volume on a daily basis. The research test utilized the paired t-test method. The results of this research indicate that the ISRA announcement does not affect the abnormal return and stock trading volume, as seen from the absence of differences in abnormal return and stock trading volume before and after the date of the announcement